Motivations and Challenges in Learning Hiragana Among Filipino University Students: An Explanatory Sequential Mixed-Methods Study - Jhon Mark S. Martinez; Miguel L. Aquino (Universitas Negeri Padang, 2026)
Foreign language learning in higher education has become increasingly important as universities respond to internationalization, global labor mobility, and the need to prepare students for intercultural engagement. In the Philippine context, Japanese language instruction has gained relevance, yet limited research has examined how Filipino students experience early Japanese script learning, particularly Hiragana, through reflective narratives. This study explored the motivations and challenges of college students learning Hiragana in a foreign language course at Isabela State University–Angadanan Campus during the first semester of School Year 2025–2026. Guided by the description phase of Gibbs’ Reflective Cycle, the study employed an explanatory sequential mixed-methods design. Quantitative data were collected from 75 students using a validated motivation questionnaire, while qualitative data were drawn from students’ reflection papers and analyzed thematically. Findings showed high overall motivation, with the strongest dimensions being the desire to become a global citizen and career and economic enhancement. Motivation did not significantly differ by sex or academic program, although ethnicity influenced career-related and global motivations. Qualitative results revealed motivations linked to employment, migration, cultural curiosity, media exposure, academic obligation, and personal growth. Students also faced challenges in memorization, character similarity, writing fatigue, time pressure, and self-comparison, but persistence, teacher support, and peer assistance supported their progress. The study highlights Hiragana learning as both a meaningful and demanding process, underscoring the value of reflective and well-scaffolded approaches in Japanese language instruction.